Current State and Prospects of the Social and Market Research in Russia - Spirina, Marina (Journal of Economic Sociology, 2014)
The round table “Current State and Prospects of the Social and Market Research in Russia” was held April 4, 2014 as a part of the XV April International Academic Conference on Economic and Social Development, HSE (Moscow). Two main presentations were made by Sergey Protsenko (South-Russian Research Center “Factor”; Association of Regional Sociological Centers “Group 7/89”) and Andrey Yakovlev (Institute for Industrial and Market Studies, HSE; Association of Russian Economic Think Tanks (ARETT)). The round table chaired by Alexander Chepurenko (dean of the Faculty of Sociology, HSE) was also attended by Vasily Tokarev (Center “ANALYST”, Volgograd), Vladimir Zvonovsky (Social surveys fund, Samara), Alexander Demidov (GFK, Moscow), Oleg Dembo (“O+K”, international research association ESOMAR, St. Petersburg), Igor Zadorin (ZIRCON, Moscow), Stepan Lvov (Russian Public Opinion Research Center, Moscow), Vadim Radaev (Laboratory for Studies in Economic Sociology, HSE, Moscow), etc. The main subject of the round table was the changes in the structure and development trends in the Russian sociological research market. Paradoxically, today sociological research industry in Russia remains poorly studied, despite the fact that its members are engaged in active exploration of other markets and services. As Alexander Chepurenko noted “The cobbler always wears the worst shoes.” This statement perfectly reflects the current situation of Russian sociologists who have little to say about the market size and the composition of members as well as about the general idea of the major problems faced by Russian research companies nowadays. The article represents the current state and main types of participants of Russian market for sociological research, describes the main trends as well as the key issues, challenges and solutions in the industry and provides the market prospects in the near future.